Animated Educational Strategy to Enhance Contraceptive Awareness and Uptake Intention Among Women of Childbearing Age: A Quasi Experimental Study - Mirnawati Mirnawati; Mardiana Ahmad; Andi Nilawati Usman; Darmawansyah Darmawansyah (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Unmet contraceptive needs among women of childbearing age remain a challenge for family planning programs in Indonesia, mainly due to low levels of knowledge and interest. Animated videos have the potential to be an effective, engaging, and easy-to-understand educational tool for conveying reproductive health information. The aim of this research is to determine the effect of animated video media on contraceptive knowledge and interest among women of childbearing age with high unmet need. Methods: A quasi-experimental pretest-posttest study with a control group was conducted on 86 respondents, divided into an intervention group (animated video) and a control group (flip chart). The research instruments were questionnaires on contraceptive knowledge and interest. The intervention was carried out for 3 weeks in two community health centers in the South Sorong region (Moswaren, Teminabuan). Data were analyzed using Chi-square, Wilcoxon, and Mann-Whitney tests. A quasi-experimental study was conducted among 86 women of childbearing age at Moswaren Health Center, divided into an intervention group (animated video, n = 43) and a control group (flip chart, n = 43). Pre- and post-test scores within groups were analyzed using Wilcoxon tests, with effect sizes (r) calculated for significant changes. Post-test scores between groups were compared using Mann-Whitney tests, and categorical outcomes were analyzed using Chi-square tests; nonsignificant results were explicitly reported to ensure interpretive transparency Results: There was a significant increase in knowledge and interest scores after education using animated videos in the intervention group, compared with the control group, the difference was statistically significant (p = 0.001). Animated videos proved to be more interesting and easier to understand for women of childbearing age, and encouraged an increase in their intention to use contraception compared to flip charts, which are passive. Conclusion: The use of animated video media in contraceptive education was proven to be effective in increasing knowledge and interest among reproductive aged women with a high unmet need for contraception. This media is recommended as an educational strategy in family planning programs in areas with limited access and low literacy.